Reconstruction of the vena cava with the peritoneum: The effect of temporary distal arteriovenous fistula on patency - (An experimental study) - Cekirdekci, A; Bayar, MK; Yilmaz, S; Cihangiroglu, M; Ayan, E; Duran, M; Gokce, O (W B Saunders Co Ltd, 2004)
Objective: To determine the effect of increasing inferior vena cava blood flow by means of distal arteriovenous fistula on the patency of a peritoneal tube graft. Materials and methods: In 16 mongrel dogs, a 3-4 cm long circular defect was created at the infrarenal inferior vena cava. The defect was interposed with peritoneal tube graft. A temporary distal femoro-femoral arteriovenous fistula was also constructed in 8 dogs just after the caval interposition. Graft patency was evaluated by Doppler ultrasonography and angiography. Histological evaluation was also performed. Results: Seven dogs in each group survived. All control grafts occluded within the first week, compared to no occlusions in fistula group (Fisher's exact test, p < 0.005). However one 'fistula' dog with a still patent graft was sacrificed on the 18th day due to ultrasonographically occluded arteriovenous fistula. Conclusion: In dogs, the peritoneum may be used as graft material for reconstruction of the inferior vena cava, provided a distal arteriovenous fistula is constructed.
52nd International Congress of the European-Society-for-Cardiovascular-Surgery -- NOV, 2003 -- ISTANBUL, TURKEY
Keywords: peritoneum; inferior vena cava; temporary arteriovenous fistula